A STUDY ON ATTRIBUTABLE RISK FACTORS OF PREDIABETES WITH REFERENCE TO COIMBATORE POPULATION - Shanmugam, Shanmugam; Jat, Rakesh Kumar (Journal of Drug Delivery and Therapeutics, 2017)
The DM patients glucose level alteration results indicated to some extent increased Glucose level with DM ( 19.1 ± 0.0 ), Type-I DM ( 74.5 ± 2.74 ), T-II DM  ( 173.5 ± 6.85 ) when compared  to regular well-fit volunteer ( 125.7 ± 2.73 ) &  40-50 years age groups of the patients were higher prevalence of DM ( 553 Numbers & 36.9 % ). Non Vegetarian are exaggerated more numbers & percentage of DM (542 Numbers & 36.1 %) when compare to Vegetarian (958 Numbers & 63.9 %) & also prominently affected DM with professional workers (540 Numbers & 36 %).  Comparatively, 80-100 Kgs body weight of DM patient’s prevalence increased in Coimbatore zone. The results of collected blood samples were expressed in the form of TCH levels DM + inflammation ( 35.1 ± 0.484↑), subsequent to drugs taken potassium levels DM associated diseases such as  hypertension ( 0.590 ± 0.02543↑ ), PTP levels exposed that the DM + hyperlipidemic  ( 1 ± 0.0296↑ ),   myocardial infarctions ( 16.94  ± 0.4321↑ ) patients SGOT levels, sodium levels DM linked diseases such as DM + bradycardia  ( 7.2 ± 0.2453↑ ), DM + congestive heart failure ( 980 ± 0.61 ↑ ) numbers of WBC, ( 12.6 ± 1.882 ) were  HB elevated more, HDL variability results have shown DM + hyperlipidemic ( 0.78 ± 1.4252↓ ), RBC count indicated DM + inflammation ( 0.269  ± 0.08105↓ ), have shown  DM & associated diseases patients after the drugs taken LDL levels for hypertension ( 33.8 ± 3.291↓ )  & subsequent to the drugs taken DM + inflammation ( 1.65  ± 0.0032↓ ). Keywords: Diabetes mellitus, glucose, type I patients, type II patients.